CONTENT ANALYSIS: EXPLORING THE SUITABILITY OF BUSINESS ENGLISH TEXTBOOK FROM LEARNER’S PERSPECTIVE - Pangulu Sudarta Saat; Endry Boeriswati; Yumna Rasjid (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACT This research aims to find out how the following aspects of analysis in textbook evaluation can facilitate assessment of the suitability of the text book students have been using as the main course book. The aspects are (1) use of business language skills and grammar (2) business vocabulary (3) business related materials (4) pedagogic features.The textbook being referred to is Market Leader, Third edition, Elementary published by Pearson Education, London, United Kingdom. The gap filled in this research and prior research is that they are prior-use textbook evaluation, while this article is based on a in-use textbook evaluation. To achieve the aim, this research employs Philipp Mayring’s Qualitative Content Analysis research method, and Chengqian Guo’s new text book evaluation model as the framework developed from previous evaluation models. Keywords: Business English text book suitability; Content Analysis; Textbook evaluation; Phillpp Mayring’s Content Analysis; Chengqian Guo’s New Textbook Evaluation Model